Serological diagnosis of pulmonary Mycobacterium tuberculosis infection by LIPS using a multiple antigen mixture. Issue 1 (December 2015) - Burbelo, Peter; Keller, Jason; Wagner, Jason; Klimavicz, James; Bayat, Ahmad; Rhodes, Craig; Diarra, Bassirou; Chetchotisakd, Ploenchan; Suputtamongkol, Yupin; Kiertiburanakul, Sasisopin; Holland, Steven; Browne, Sarah; et al.
Abstract Background There is an urgent need for a simple and accurate test for the diagnosis of human Mycobacterium tuberculosis, the infectious agent causing tuberculosis (TB). Here we describe a serological test based on light emitting recombinant proteins for the diagnosis of pulmonaryMycobacterium tuberculosis infection. Methods Luciferase Immunoprecipitation Systems (LIPS), a fluid-phase immunoassay, was used to examine antibody responses against a panel of 24 different M. tuberculosis proteins. Three different strategies were used for generating the constructs expressing the recombinant fusion M. tuberculosis proteins with luciferase: synthetic gene synthesis, Gateway recombination cloning, and custom PCR synthesis. A pilot cohort of African pulmonary TB patients was used for initial antibody screening and confirmatory studies with selected antigens were performed with a cohort from Thailand and healthy US blood donors. In addition to testing M. tuberculosis antigens separately, a mixture that tested seven antigens simultaneously was evaluated for diagnostic performance. Results LIPS testing of a pilot set of serum samples from African pulmonary TB patients identified a potential subset of diagnostically usefulM. tuberculosis antigens. Evaluation of a second independent cohort from Thailand validated highly significant antibody responses against seven antigens (PstS1, Rv0831c, FbpA, EspB, bfrB, HspX and ssb), which often showed robust antibody levels up to 50- to 1000-fold higher than local community controls. Marked heterogeneity of antibody responses was observed in the patients and the combined results demonstrated 73.5 % sensitivity and 100 % specificity for detection of pulmonary TB. A LIPS test simultaneously employing the sevenM. tuberculosis antigen as a mixture matched the combined diagnostic performance of the separate tests, but showed an even higher diagnostic sensitivity (90 %) when a cut-off based on healthy US blood donors was used. Conclusion A LIPS immunoassay employing multipleM. tuberculosis antigens shows promise for the rapid and quantitative serological detection of pulmonary TB.